Do the poor elderly benefit more than the non-poor elderly from growth? evidence from urban China. Issue 10 (6th June 2020) - Wang, Zuobao; Sun, Jing
ABSTRACT: This paper evaluates whether the poor elderly benefited more than the non-poor elderly from growth in urban China between 2005 and 2015. The results show that although elderly income in urban China has increased overall, the poor elderly benefited less than the non-poor elderly. Growth is absolutely pro-poor but not relatively pro-poor, which has slowed the process of poverty reduction.